Needs Analysis of AI-based Smart English Conversation Application for EFL and Students with Disabilities - Sari, Fitriana Kartika; Kurniawan, Prasetyo Yuli; Savitri, Andini Syita (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study aimed to analyze the needs of EFL students and students with disabilities for the development of a Smart English Conversation application based on AI. Using a descriptive qualitative approach, data were collected through interviews with three English lecturers teaching inclusive classes and 60 of EFL students and 20 students of disabilities. he results revealed that lecturers acknowledged the potential of AI-based media to enhance speaking skills but had limited experience integrating them due to access restrictions and reliance on conventional materials such as textbooks and slides. Students reported several challenges in conventional learning, including lack of confidence, limited practice opportunities, insufficient disability-friendly media, and restricted lecturer time for individual feedback. Needs analysis indicated a very high demand for AI-based applications supporting speaking skills. Key features identified included adaptive speech recognition, real-time automatic feedback, inclusive accessibility features, real-life conversational simulations, and personalized learning materials. The findings highlight the urgency of developing an AI-based Smart English Conversation application that prioritizes inclusivity, interactivity, adaptability, and real-time feedback, while also integrating gamification and compatibility with existing online learning platforms.